Polygonatum cyrtonema Hua polysaccharides alleviate muscle atrophy and fat lipolysis by regulating the gut microenvironment in chemotherapy-induced cachexia - Zhou, Rongrong; Liu, Tingting; Qin, You; Xie, Jing; Zhang, Shuihan; Xie, Yi; Lao, Jia; He, Wei; Zeng, Hongliang; Tang, Xueyang; Tian, Xuefei; Qin, Yuhui (Frontiers in Pharmacology, 2025)
Introduction:Polygonatum cyrtonema Hua (PC) is an essential herbal medicine in China, known for improving muscle quality and enhancing physical function; its active ingredients are polysaccharides (PCPs). A previous study revealed the anti-atrophy effects of PCPs in cachectic mice. However, whether the effects of PCPs on anti-atrophy are associated with gut microenvironment remain elusive. This research endeavored to assess the medicinal efficacy of PCPs in alleviating muscle atrophy and fat lipolysis and explore the potential mechanisms.Methods: A cancer cachexia model was induced by male C57BL/6 mice bearing Lewis lung tumor cells and chemotherapy. The pharmacodynamics of PCPs (32 and 64 mg/kg/day) was investigated through measurements of tumor-free body weight, gastrocnemius muscle weight, soleus muscle weight, epididymal fat weight, tissue histology analysis, and pro-inflammatory cytokines. Immunohistochemistry and Western blotting assays were further used to confirm the effects of PCPs. 16S rRNA sequencing, LC-MS and GC-MS-based metabolomics were used to analyze the gut microbiota composition and metabolite alterations. Additionally, the agonist of free fatty acid receptor 2 (FFAR2)—a crucial short-chain fatty acid (SCFA) signaling molecule—was used to investigate the role of gut microbiota metabolites, specifically SCFAs, in the treatment of cancer cachexia, with comparisons to PCPs.Results: This study demonstrated that PCPs significantly mitigated body weight loss, restored muscle fiber atrophy and mitochondrial disorder, alleviated adipose tissue wasting, strengthened the intestinal barrier integrity, and decreased the intestinal inflammation in chemotherapy-induced cachexia. Furthermore, the reversal of specific bacterial taxa including Klebsiella, Akkermansia, norank_f__Desulfovibrionaceae, Enterococcus, NK4A214_group, Eubacterium_fissicatena_group, Eubacterium_nodatum_group, Erysipelatoclostridium, Lactobacillus, Monoglobus, Ruminococcus, Odoribacter, and Enterorhabdus, along with alterations in metabolites such as amino acids (AAs), eicosanoids, lactic acid and (SCFAs), contributed to the therapeutic effects of PCPs.Conclusion: Our findings suggest that PCPs can be used as prebiotic drugs targeting the microbiome–metabolomics axis in cancer patients undergoing chemotherapy.